Fertilization of high-yield corn with poultry litter based on nitrogen doses - Corrêa, Juliano Corulli; Grohskopf, Marco André; Rebellatto, Agostinho; Rigo, Amanda Zolet; Coldebella, Arlei (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to recommend nitrogen doses from poultry litter-based organic fertilizers in powder and pellet forms, compared with mineral fertilizer, in a high-yield corn crop under no-tillage. The treatments consisted of a 3×3+1 factorial arrangement, with: three fertilizers, two organic derived from poultry litter in powder (OPo) and pelletized (OPe) forms and one mineral fertilizer (M); three N doses of 65, 100, and 135% of the recommended N requirement for corn; and an unfertilized control. After five corn crops farmed under no-tillage in a Rhodic Kandiudox, the recommended doses for fertilization with poultry litter organic fertilizers, with an expected yield equal to or greater than 8,000 kg ha-1, could be achieved from doses of 100 kg ha-1 N in OPe and M and of 121 kg ha-1 N in OPo. Increasing doses of the OPe, OPo, and M fertilizers raise the contents of organic carbon, N, and available P in the surface soil layer (0.0–0.1 m) and of exchangeable K up to a depth of 0.2 m, allowing to obtain N, P, and K contents in the plant tissue within the sufficiency range of the corn crop.